EUTHANASIA WITH REGARDS IN EGYPT SHARIA - Zahra Hamedani; Seyed Milad Alizadeh Javaheri (European Scientific Journal, ESJ, 2014)
Many advocates of euthanasia consider the criminal law to be an inappropriate medium to adjudicate the profound ethical and humanitarian dilemmas associated with end of life decisions. This work examines the legal response to euthanasia and end of life decisions and considers whether legal reform is an appropriate response to calls for euthanasia to be more readily available as a mechanism for providing death with dignity. Through an analysis of consent to treatment and medical decision making, euthanasia is carefully located within its legal, medical, and social contexts. This book focuses on the impact of euthanasia on the dignity of both the recipient and the practitioner while emphasizing the legal, professional, and ethical implications of euthanasia and its significance for the exercise of clinical discretion.